Super-hydrophilic photo-thermal conversion stainless steel mesh and preparation method thereof

By modifying the stainless steel mesh with Cu, Au, and TCNQ, a super hydrophilic photothermal conversion stainless steel mesh is prepared, which solves the problem of corrosion of oil-water separation materials in complex environments, and realizes the degradation of organic dyes and seawater desalination, significantly improving the acquisition efficiency of freshwater resources.

CN119615157AInactive Publication Date: 2025-03-14SOUTHWEST PETROLEUM UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411901725.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-23
Publication Date
2025-03-14
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Existing oil-water separation materials are prone to corrosion in complex use environments and are difficult to effectively remove organic dyes in water bodies. There is a lack of research on obtaining fresh water by using light-heat conversion.

Method used

Through electroplating, electrochemical plating and hydrothermal reaction, Cu, Au, TCNQ modified photothermal conversion stainless steel mesh is prepared to realize its super hydrophilicity and photothermal conversion functions.

Benefits of technology

This material can effectively separate oil and water emulsion, degrade organic dyes, and desalinate seawater through photothermal conversion, significantly improving the acquisition efficiency of freshwater resources.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119615157A_ABST
    Figure CN119615157A_ABST
Patent Text Reader

Abstract

The invention discloses a super-hydrophilic photothermal conversion stainless steel mesh and a preparation method thereof, and belongs to the field of plating of metal materials. The preparation method of the super-hydrophilic photo-thermal conversion stainless steel mesh comprises the following steps: cleaning the stainless steel mesh; preparing a copper sulfate solution and carrying out electroplating and chemical plating; preparing a TCNQ acetonitrile solution and carrying out hydrothermal reaction; preparing a KAuBr4 aqueous solution and carrying out hydrothermal reaction; the super-hydrophilic photo-thermal conversion stainless steel mesh prepared by the invention can be used for oil-water separation, dye degradation and seawater desalination; moreover, pure water can be collected from a seawater solution containing heavy metal ions, a crude oil emulsion and a system containing dye wastewater, and the method has a good application prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of photothermal conversion, and in particular to a super-hydrophilic photothermal conversion stainless steel mesh and a preparation method thereof. Background Art

[0002] In recent decades, with the booming shipping industry and the exploitation of offshore oil, marine oil spills have occurred frequently, causing great damage to the environment and ecosystem. Oil-water separation materials have super-wettability such as super-hydrophobicity (referring to a surface with a contact angle with water greater than 150° and a sliding angle less than 10°) or super-hydrophilicity (referring to a surface with a contact angle with water less than 5°), which provides a simple, effective and practical method for efficient separation of oil and water. At present, oil-water separation materials are mainly concentrated in fabrics, sponge foams, aerogels, membranes, and metal meshes. Among them, metal meshes have great application potential in the field of oil-water separation due to their easy availability, superior mechanical properties, high wear resistance, and other characteristics.

[0003] In actual use environment, separation materials may be in a complex use environment (acid, alkali, salt), which may cause corrosion of the materials and affect their separation performance and service life. In addition, oily wastewater often has complex components, such as some organic dyes that are difficult to separate. Therefore, how to effectively remove organic dyes from water is also a major research hotspot in the field of water treatment.

[0004] Most of the water supply for coastal communities around the world has traditionally come from inland or nearshore freshwater resources - groundwater aquifers, rivers and lakes. However, changing climate patterns, coupled with the pressure of population growth and the limited supply of new cheap freshwater, are shifting the water industry's attention to a new trend, that is, more and more coastal cities and utility companies are looking to the ocean for freshwater. Considering the current deteriorating water environment, when oil, organic dyes and seawater are in the same system, how to effectively obtain freshwater is still an area of ​​little research. The use of photothermal conversion to obtain freshwater is a sustainable and promising way to develop freshwater resources.

[0005] Therefore, the art expects to develop a super-hydrophilic photothermal conversion stainless steel mesh that can not only separate various oil-water emulsions, degrade organic dyes in water bodies, but also utilize photothermal conversion for complex seawater desalination. Summary of the invention

[0006] The purpose of the present invention is to provide a super-hydrophilic photothermal conversion stainless steel mesh and a preparation method thereof. The super-hydrophilic photothermal conversion stainless steel mesh obtained by simple electroplating, chemical plating and hydrothermal reaction can be used to treat various complex oily wastewaters.

[0007] The technical solution of the present invention is as follows: S1. Soak a 2*2 cm stainless steel mesh in acetone, ethanol, and pure water successively, and ultrasonically clean each mesh for 10 min; S2. Weigh 0.24 g of copper sulfate and dissolve it in 100 mL of deionized water to obtain a copper sulfate solution; measure 1 mL of sulfuric acid with a concentration of 0.5 mol / L and add it to the obtained copper sulfate solution to obtain an electroplating solution; place the stainless steel mesh obtained in S1 in the obtained copper sulfate solution, electroplate it at a voltage of 600 mV for 8 min, and then take it out to obtain a Cu-plated stainless steel mesh; S3. Weigh 0.5 g of copper sulfate, 1.5 g of disodium ethylenediaminetetraacetate, and 0.4 g of sodium hydroxide, respectively, and dissolve them in 100 mL of deionized water to obtain a mixed solution; measure 15 mL of 10% ammonia water by mass and add it to the obtained mixed solution to obtain a chemical plating solution; S4. The Cu-plated stainless steel mesh obtained from S2 and the chemical plating solution obtained from S3 were placed in a beaker and subjected to a hydrothermal reaction at a temperature of 60 ° C for 2h, and then removed to obtain a stainless steel mesh after chemical plating; S5. Weigh 0.05 g of TCNQ and dissolve it in 50 mL of acetonitrile to obtain a TCNQ solution; place the chemically plated stainless steel mesh obtained in S4 together with the TCNQ solution in a beaker, react at a temperature of 30°C for 1 hour, then take out and dry to obtain a Cu (TCNQ) modified stainless steel mesh; S6. Weigh 0.008 g of potassium tetrabromoaurate and dissolve it in 20 mL of deionized water to obtain a potassium tetrabromoaurate solution. Place the stainless steel mesh after TCNQ reaction together with the potassium tetrabromoaurate solution in a beaker, react at 30°C for 2 hours, and then take it out. Obtain Au-doped Cu (TCNQ) modified stainless steel mesh, which is a super hydrophilic photothermal conversion stainless steel mesh.

[0008] In summary, due to the adoption of the above technical solution, the beneficial effects of the present invention are: 1. The present invention obtains a Cu, Au, TCNQ modified photothermal conversion stainless steel mesh through electroplating, chemical plating and simple hydrothermal reaction. The reaction is mild and easy to operate and carry out.

[0009] 2. The stainless steel mesh used in the present invention, after being modified by Cu, Au, and TCNQ, has a significantly changed pore size, and can effectively separate oil-in-water emulsions.

[0010] 3. The photothermal conversion stainless steel mesh obtained by the present invention can degrade organic dyes in water bodies and perform efficient photothermal conversion to desalinate seawater. It can also collect pure water from seawater solutions containing heavy metal ions, crude oil emulsions and dye-containing wastewater systems. BRIEF DESCRIPTION OF THE DRAWINGS

[0011] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments will be briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and should not be regarded as limiting the scope.

[0012] Image Description Figure 1 : These are scanning electron microscope morphology images of the stainless steel mesh in Example 1 at various stages, wherein a, a' are low-magnification and high-magnification surface morphologies of the stainless steel mesh, and a'' is a cross-section of the stainless steel mesh; b, b' are low-magnification and high-magnification surface morphologies of the Cu-plated stainless steel mesh, and b'' is a cross-section of the Cu-plated stainless steel mesh; c, c' are low-magnification and high-magnification surface morphologies of the Cu (TCNQ) modified stainless steel mesh, and c'' is a cross-section of the Cu (TCNQ) modified stainless steel mesh; d, d' are low-magnification and high-magnification surface morphologies of the Au-doped Cu (TCNQ) modified stainless steel mesh, and d'' is a cross-section of the Au-doped Cu (TCNQ) modified stainless steel mesh.

[0013] Figure 2 The wettability of the stainless steel mesh, Cu-plated stainless steel mesh, Cu (TCNQ)-modified stainless steel mesh, and Au-doped Cu (TCNQ)-modified stainless steel mesh in the preparation process of Example 1 to different liquids; Figure 3 a(i) is an optical photo of the oil-water separation device. Figure 3 a(ii) is an optical photograph of a surfactant-free water-in-oil emulsion before and after separation. Figure 3 a (iii) Optical photographs of surfactant-stabilized oil-in-water emulsion before and after separation Figure 3 b is the flux and separation efficiency of the super-hydrophilic photothermal conversion stainless steel mesh for different oil emulsions in water without surfactant in Example 1, Figure 3 c is the flux and separation efficiency of the super-hydrophilic photothermal conversion stainless steel mesh for different oil-in-water emulsions stabilized by surfactants in Example 1, Figure 3 d is the flux and separation efficiency of the super-hydrophilic photothermal conversion stainless steel mesh for different oil-in-water emulsions under complex environment in Example 1; Figure 4 a is the light absorption performance of the super-hydrophilic photothermal conversion stainless steel mesh at each stage. Figure 4 b is the energy band of the super-hydrophilic photothermal conversion stainless steel mesh at each stage. Figure 4 c is the photothermal response temperature-time curve of the super-hydrophilic photothermal conversion stainless steel mesh under dry and wet conditions. Figure 4 d Infrared thermal imaging of super hydrophilic photothermal conversion stainless steel mesh; Figure 5a is a schematic diagram of the super-hydrophilic photothermal conversion stainless steel mesh seawater desalination device prepared in Example 1, Figure 5 b is the real-time mass change curve of the super-hydrophilic photothermal conversion stainless steel mesh. Figure 5 c is the quality change curve of the super-hydrophilic photothermal conversion stainless steel mesh in the long-term seawater desalination test. Figure 5 d is the salinity of the water before and after evaporation of the super-hydrophilic photothermal conversion stainless steel mesh; Figure 6 a is a photo of the super-hydrophilic photothermal conversion stainless steel mesh prepared in Example 1 and used for photocatalytic degradation of methylene blue dye solution at different times, Figure 6 b is the absorption spectra of the dye solution of the super-hydrophilic photothermal conversion stainless steel mesh prepared in Example 1 for photocatalytic degradation of methylene blue dye at different times; Figure 7 a is a photocatalytic mechanism diagram of the photothermal conversion stainless steel mesh prepared in Example 1, Figure 7 b is the concentration of heavy metal ions in the desalinated seawater before and after desalination, Figure 7 c is the transmittance of the surfactant-stabilized crude oil-in-water emulsion before and after dilution, Figure 7 d is the absorbance of the surfactant-stabilized water-in-crude oil emulsion containing methylene blue before and after dilution. Figure 7 e is the absorbance of the surfactant-stabilized water-in-crude oil emulsion containing Rhodamine B before and after dilution. Figure 7 f is the real-time mass change curve of the three solutions. Figure 7 g is the microscopic photo of the three emulsions before and after fading. Figure 7 h is the total organic carbon content of the three emulsions before and after desalination, Figure 7 i is the oil removal rate of the three emulsions after desalination.

[0014] FIG8 is a schematic diagram of the preparation process of the present invention. DETAILED DESCRIPTION

[0015] In order to make the purpose, technical scheme and advantages of the present invention more clear, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention, that is, the embodiments described are only part of the embodiments of the present invention, rather than all the embodiments.

[0016] Therefore, the following detailed description of the embodiments of the present invention is not intended to limit the scope of the claimed invention, but merely represents selected embodiments of the present invention. Based on the embodiments of the present invention, those skilled in the art can select within a suitable range through the description of the text.

[0017] The features and performance of the present invention are further described in detail below in conjunction with the embodiments.

[0018] Example 1

[0019] A preferred embodiment of the present invention provides a method for preparing a photothermal conversion stainless steel mesh, and the specific steps are as follows: (1) Cut a 2 cm × 2 cm stainless steel mesh and ultrasonically clean it in acetone, ethanol, and water for 10 minutes.

[0020] (2) Weigh 0.24 g of copper sulfate and dissolve it in 100 mL of deionized water. Add 1 mL of 0.5 mol / L sulfuric acid to prepare the electroplating solution.

[0021] (3) The cleaned stainless steel mesh was electroplated for 8 min at a voltage of 600 mV and then immediately removed.

[0022] (4) Weigh 0.5 g of copper sulfate, 1.5 g of disodium ethylenediaminetetraacetate, and 0.4 g of sodium hydroxide respectively and dissolve them in 100 mL of deionized water. Then, add 15 mL of 10 wt.% ammonia water to prepare an electroless plating solution.

[0023] (5) The electroplated stainless steel mesh is subjected to chemical plating for 2 h at a temperature of 60°C, and then immediately taken out.

[0024] (6) Weigh 0.05 g of TCNQ and dissolve it in 50 mL of acetonitrile solution.

[0025] (7) The electrolessly plated stainless steel mesh was placed in a TCNQ acetonitrile solution for treatment at a reaction temperature of 30 °C and for 1 h, and then immediately removed.

[0026] (8) Weigh 0.008 g of potassium tetrabromoaurate and dissolve it in 30 mL of deionized water.

[0027] (9) The stainless steel mesh with hydrothermally grown TCNQ was placed in a gold salt aqueous solution at a reaction temperature and time of 30 °C and 2 h, respectively, and then immediately taken out.

[0028] Each stage of the photothermal conversion stainless steel mesh prepared in Example 1 was analyzed by scanning electron microscope. Figure 1 a is the original stainless steel mesh with a smooth surface; Figure 1 b is the morphology of the stainless steel mesh after copper plating. It can be seen that the surface of the stainless steel mesh is completely covered by a large number of copper particles with a diameter of about 1 μm, and the diameter of the steel wire increases to about 25 μm. After further TCNQ modification, Figure 1 As shown in c, many rod-like structures with a diameter of 1-10 μm are generated on the surface. 4 After treatment, a large number of gold nanoparticles appeared on the surface ( Figure 1 d).

[0029] The various stages of the photothermal conversion stainless steel mesh prepared in Example 1 were tested for wettability using a contact angle tester. The results are as follows: Figure 2 As shown. Figure 2 As shown in a, the original stainless steel mesh exhibits hydrophobic, oleophilic, and amphiphilic properties in liquid. After modification, it exhibits super amphiphilic properties in air and super amphiphilic properties in liquid, and the contact angle in liquid gradually increases ( Figure 2 bd).

[0030] The photothermal conversion stainless steel mesh prepared in Example 1 was fixed on the glass tube. Under the action of the suction pump, the modified stainless steel mesh achieved emulsion separation. The results are shown in FIG. Figure 3 As shown. Figure 3 a It can be seen that after separation, the emulsion changes from opaque milky white to transparent colorless, indicating that the oil droplets are trapped. Further calculation of the separation efficiency shows that for the emulsion without surfactant, the separation efficiency is higher than 99.84% ( Figure 3 b), after adding surfactant, the separation efficiency decreased, but was still higher than 99.81% ( Figure 3 c). In corrosive environments (acid, alkali, salt), it still maintains excellent separation capabilities ( Figure 3 d).

[0031] The light absorption capacity and light-to-heat conversion capacity of the photothermal conversion stainless steel mesh prepared in Example 1 were studied by UV-visible diffuse reflectance spectroscopy and infrared thermal imaging, respectively. The results are as follows: Figure 4 As shown. Figure 4 a It can be seen that after adding TCNQ and Au nanoparticles, the light absorption capacity of the sample is greatly improved, and the energy band is also greatly reduced ( Figure 4 b). The calculation formula of energy band is as follows:

[0032] α is the light absorption index, ν is the light frequency, h is Planck's constant, A is the number, E g is the bandgap width of the semiconductor.

[0033] The photothermal conversion stainless steel mesh prepared in Example 1 was used in a homemade seawater desalination device ( Figure 5 a) The desalination capacity of seawater was studied and the results are as follows Figure 5 Figure 5b shows the mass changes of pure water and modified water at different stages under sunlight. After one hour of illumination, the maximum evaporation value can reach 3.30 Kg / m 2 The desalination capacity of the modified stainless steel mesh remained stable after five cycles ( Figure 5 c). After desalination, Na + , K+ , Ca 2+ Mg 2+ The concentrations are all below the World Health Organization's standard values ​​for ion concentrations in drinking water ( Figure 5 d).

[0034] The photothermal conversion stainless steel mesh prepared in Example 1 was used to study the catalytic degradation ability of methylene blue dye in water by simulating sunlight with a xenon lamp, and the concentration of methylene blue in water during the degradation process was tested by ultraviolet absorption spectroscopy. The results are as follows: Figure 6 As shown. First, stir in the dark for 1 hour to reach adsorption-desorption equilibrium. Then collect samples every 20 minutes and test them. It can be seen that at 80 minutes, the solution becomes colorless ( Figure 6 a), and there is no absorption peak of methylene blue in the absorption spectrum ( Figure 6 b).

[0035] In order to further study the excellent water purification ability of the modified stainless steel mesh prepared in Example 1, high-concentration heavy metal simulated wastewater was purified. Figure 7 As shown in b, after solar evaporation, the concentration of heavy metal ions is reduced by 5-6 orders of magnitude. Crude oil / brine emulsion is further used for purification. Figure 7 As shown in Figure c, after solar evaporation, the originally turbid emulsion was purified into a clear and transparent liquid, and the transmittance changed from 1% to nearly 100%. In addition, crude oil / brine emulsions containing MB and RB were also selected to verify the wastewater treatment behavior of the water purification system. Figure 7 As shown in d and e, the concentration of dye molecules is almost zero after solar-driven water evaporation, as judged by the disappearance of the absorption peak in the UV-visible spectrum. The total organic carbon (TOC) content in different emulsions and collected water was also tested. Figure 7 f also shows the optical microscope pictures before and after desalination, demonstrating the excellent desalination ability of the complex oil-containing brine. Figure 7 g shows that the mass changes of different emulsions after one hour of exposure to sunlight are 2.58 Kg / m 2 , 2.28 Kg / m 2 , 2.07 Kg / m 2 . Figure 7 h gives the TOC values ​​of crude oil / brine emulsion (3781.2 ppm), crude oil / brine emulsion containing MB (3752.1 ppm) and RB (3773.5 ppm), and the corresponding collected water (4.0 ppm), (4.9 ppm), and (3.6 ppm), respectively. The calculated separation efficiency is as high as 99.86% ( Figure 7 i), indicating that the modified stainless steel mesh has excellent purification performance for oil-in-water emulsions regardless of the contaminants in the feed liquid.

[0036] The super-hydrophilic photothermal conversion stainless steel mesh obtained in Example 1 has a water contact angle and an oil contact angle in the air of 0°, an underwater oil contact angle and an oil underwater water contact angle of 158°, showing super-amphiphobicity in the air and super-amphiphobicity underwater.

[0037] The super-hydrophilic photothermal conversion stainless steel mesh obtained in Example 1 can absorb more than 90% of light at 200-2000nm, and the band gap is 0.87eV; after irradiation for 60 minutes under the intensity of one sun, the temperature of the super-hydrophilic photothermal conversion stainless steel mesh can reach 84.8°C in a dry state and 44.2°C in a wet state.

[0038] The super-hydrophilic photothermal conversion stainless steel mesh obtained in Example 1 has a methylene blue removal efficiency of not less than 99.99% in a methylene blue aqueous solution with a concentration of 10 mg / L when irradiated for 80 minutes at one sunlight intensity.

[0039] The super-hydrophilic photothermal conversion stainless steel mesh obtained in Example 1 has a separation efficiency of greater than 99.84% for surfactant-free oil-in-water emulsions, and a separation efficiency of greater than 99.81% for surfactant-stabilized oil-in-water emulsions.

[0040] The evaporation rate of seawater by the super hydrophilic photothermal conversion stainless steel mesh obtained in Example 1 under one sunlight intensity is 3.30 Kg / m 2 h 1 The evaporation rate of the seawater-crude oil emulsion is 2.58 Kg / m 2 h 1 The evaporation rate of the crude oil in seawater emulsion containing Rhodamine B is 2.28 Kg / m 2 h 1 The evaporation rate of the crude oil emulsion containing methylene blue seawater is 2.07Kg / m 2 h 1 .

[0041] Comparative Examples 2-3 FIG8 is a schematic diagram of the preparation process of the present invention.

[0042] Comparative Example 2-3 provides a super-hydrophilic photothermal conversion stainless steel mesh. Compared with Example 1, the difference is that in step (3), the electroplating time is 7 min and 9 min respectively, and the rest is the same as Example 1 and will not be repeated here.

[0043] Comparative Example 4 Comparative Example 2-3 provides a method for preparing a photothermal conversion stainless steel mesh. Compared with Example 1, the difference is that step (4) and step (5) are removed, and the rest is the same as Example 1 and will not be repeated here.

[0044] The above contents of the present invention are further detailed descriptions of the present invention in combination with specific / preferred embodiments, and it cannot be determined that the specific implementation of the present invention is limited to these descriptions. Without departing from the concept of the present invention, it is also possible to make several substitutions or modifications to these described embodiments, and these substitutions or modifications should be deemed to belong to the protection scope of the present invention.

Claims

1. A method for preparing a super-hydrophilic photothermal conversion stainless steel mesh, characterized in that: The following steps are involved: S1. Soak a 2*2 cm stainless steel mesh in acetone, ethanol, and pure water successively, and ultrasonically clean each for 10 min; S2. Weigh 0.24 g of copper sulfate and dissolve it in 100 mL of deionized water to obtain a copper sulfate solution; measure 1 mL of sulfuric acid with a concentration of 0.5 mol / L and add it to the obtained copper sulfate solution to obtain an electroplating solution; place the stainless steel mesh obtained in S1 in the obtained copper sulfate solution, electroplate it at a voltage of 600 mV for 8 min, and then take it out to obtain a Cu-plated stainless steel mesh; S3. Weigh 0.5 g of copper sulfate, 1.5 g of disodium ethylenediaminetetraacetate, and 0.4 g of sodium hydroxide, respectively, and dissolve them in 100 mL of deionized water to obtain a mixed solution; measure 15 mL of 10% ammonia water by mass and add it to the obtained mixed solution to obtain a chemical plating solution; S4. The Cu-plated stainless steel mesh obtained from S2 and the chemical plating solution obtained from S3 were placed in a beaker and subjected to a hydrothermal reaction at a temperature of 60 ° C for 2h, and then removed to obtain a stainless steel mesh after chemical plating; S5. Weigh 0.05 g of TCNQ and dissolve it in 50 mL of acetonitrile to obtain a TCNQ solution; place the chemically plated stainless steel mesh obtained in S4 together with the TCNQ solution in a beaker, react at a temperature of 30°C for 1 hour, then take out and dry to obtain a Cu (TCNQ) modified stainless steel mesh; S6. Weigh 0.008 g of potassium tetrabromoaurate and dissolve it in 20 mL of deionized water to obtain a potassium tetrabromoaurate solution. Place the stainless steel mesh after TCNQ reaction together with the potassium tetrabromoaurate solution in a beaker, react at 30°C for 2 hours, and then take it out. Obtain Au-doped Cu (TCNQ) modified stainless steel mesh, which is a super hydrophilic photothermal conversion stainless steel mesh.

2. A super hydrophilic photothermal conversion stainless steel mesh, characterized in that: The preparation method according to claim 1 is used to obtain the 3. The super hydrophilic photothermal conversion stainless steel mesh according to claim 2, characterized in that: The surface of the Cu-plated stainless steel mesh is coated with 1 μm copper particles, the Cu (TCNQ) modified stainless steel mesh has a rod-like structure of 1-10 μm, and the surface of the Au-doped Cu (TCNQ) modified stainless steel mesh has Au particles.

4. The super hydrophilic photothermal conversion stainless steel mesh according to claim 2, characterized in that: The water contact angle and oil contact angle of the super-hydrophilic photothermal conversion stainless steel mesh in the air are both 0°, and the underwater oil contact angle and the underwater water contact angle are both 158°.

5. The super hydrophilic photothermal conversion stainless steel mesh according to claim 2, characterized in that: The super-hydrophilic photothermal conversion stainless steel mesh can absorb more than 90% of light at 200-2000nm, and the band gap width is 0.87eV; after irradiation for 60 minutes under the intensity of one sun, the temperature of the super-hydrophilic photothermal conversion stainless steel mesh is 84.8°C in a dry state and 44.2°C in a wet state.

6. The super hydrophilic photothermal conversion stainless steel mesh according to claim 2, characterized in that: The super-hydrophilic photothermal conversion stainless steel mesh has a separation efficiency of greater than 99.84% for surfactant-free oil-in-water emulsions and a separation efficiency of greater than 99.81% for surfactant-stabilized oil-in-water emulsions.

7. The super hydrophilic photothermal conversion stainless steel mesh according to claim 2, characterized in that The super-hydrophilic photothermal conversion stainless steel mesh has a methylene blue removal efficiency of not less than 99.99% in a methylene blue aqueous solution with a concentration of 10 mg / L when irradiated for 80 minutes under one sunlight intensity.

8. The super hydrophilic photothermal conversion stainless steel mesh according to claim 2, characterized in that: The super hydrophilic photothermal conversion stainless steel mesh has an evaporation rate of 3.30 Kg / m for seawater under one sunlight intensity. 2 h 1 The evaporation rate of the seawater-crude oil emulsion is 2.58 Kg / m 2 h 1 The evaporation rate of the crude oil in seawater emulsion containing Rhodamine B is 2.28Kg / m 2 h 1 The evaporation rate of the crude oil emulsion containing methylene blue in seawater is 2.07 Kg / m 2 h 1 .